Could combination chemotherapy be more effective than monotherapy in the treatment of visceral leishmaniasis? A systematic review of preclinical evidence. Issue 6 (9th May 2022) - Bastos, Daniel S. S.; Silva, Adriana C.; Novaes, Rômulo D.; Souza, Ana Claudia F.; Santos, Eliziária C.; Gonçalves, Reggiani V.; Marques-Da-Silva, Eduardo A.
Abstract: Abstract: From a systematic review framework, we assessed the preclinical evidence on the effectiveness of drug combinations for visceral leishmaniasis (VL) treatment. Research protocol was based on the PRISMA guideline. Research records were identified from Medline, Scopus and Web of Science. Animal models, infection and treatment protocols, parasitological and immunological outcomes were analysed. The SYRCLE's (SYstematic Review Center for Laboratory Animal Experimentation) toll was used to evaluate the risk of bias in all studies reviewed. Fourteen papers using mice, hamster and dogs were identified. Leishmania donovani was frequently used to induce VL, which was treated with 23 drugs in 40 different combinations. Most combinations allowed to reduce the effective dose, cost and time of treatment, in addition to improving the parasitological control of Leishmania spp. The benefits achieved from drug combinations were associated with an increased drug's half-life, direct parasitic toxicity and improved immune defences in infected hosts. Selection, performance and detection bias were the main limitations identified. Current evidence indicates that combination chemotherapy, especially those based on classical drugs (miltefosine, amphotericin B antimony-based compounds) and new drugs (CAL-101, PAM3Cys, tufisin and DB766), develops additive or synergistic interactions, which trigger trypanocidal and immunomodulatory effects associated with reduced parasite load, organ damage and better cure rates in VL.